การจัดการสุขภาพของผู้สูงอายุโรคความดันโลหิตสูง ที่อาศัยอยู่ในชุมชนเมือง กรุงเทพมหานคร - คุ้มทวีพร, พัสมณฑ์; จิรธรรมคุณ, เสาวลักษณ์ (Journal of The Royal Thai Army Nurses, 2016)
การศึกษาครั้งนี้เป็นการวิจัยเชิงคุณภาพ ตามแนวทางการวิจัยแบบสร้างทฤษฎีจากข้อมูล เพื่อศึกษาการจัดการสุขภาพของผู้สูงอายุโรคความดันโลหิตสูงที่สามารถควบคุมค่าความดันโลหิตให้อยู่ในเกณฑ์ปกติ อาศัยในชุมชนเมือง กรุงเทพมหานครเก็บรวบรวมข้อมูลโดยการสนทนากลุ่มที่มีการบันทึกเสียงตลอดการสนทนา 7 ครั้ง วิเคราะห์ข้อมูลชนิดคำต่อคำ เพื่อสร้างแนวคำถามกึ่งโครงสร้างตามทฤษฎีระบบของลุดวีด วอน เบอร์ทาแลนฟี แล้วนำมาตรวจสอบในการสนทนากลุ่มครั้งที่ 8 ผลการวิจัยพบว่า 1. เป้าหมายในชีวิตการจัดการสุขภาพของผู้ให้ข้อมูล คือ 1) การมีสุขภาพที่แข็งแรง ปฏิบัติกิจวัตรประจำวันได้ด้วยตนเอง และไม่เป็นภาระของครอบครัว 2) การอยู่ร่วมกับกัลยาณมิตร คือ การมีคนเข้าใจและช่วยเหลือกัน 3) การมีทรัพย์สินเพียงพอ ไม่เป็นหนี้ สามารถดูแลสุขภาพตนเองได้ 2. ผู้ให้ข้อมูลมีปัจจัยนำ คือ 1) ปฏิบัติตนตามหลักอิทธิบาท 4 เสมอ 2) มีกัลยาณมิตร 3. ผู้ให้ข้อมูลระบุกระบวนการและผลลัพธ์ ดังนี้ 1) การออกกำลังกายแบบแอโรบิค 2) การงดรับประทานอาหารมัน อาหารเค็ม และเพิ่มอาหารกากใย 3) การงดดื่มสุรา 4) การลดและควบคุมน้ำหนักตัวให้อยู่ในเกณฑ์ปกติ 5) การงดสูบบุหรี่ 6) การผ่อนคลายความเครียด7) การรับประทานยารักษาโรคความดันโลหิตสูงอย่างสม่ำเสมอ 8) การดูแลซึ่งกันและกันในกลุ่มที่ป่วยเป็นโรคความดันโลหิตสูงคณะผู้วิจัยจึงเสนอให้นำแนวคิดของผู้ให้ข้อมูลเหล่านี้ไปใช้สำหรับการปฏิบัติ การศึกษา และการวิจัยต่อไป Health management of hypertension elderly in urban community, Bangkok This qualitative study was based on grounded theory method. This study aimed to examine the concept of health management in hypertension elders within Thai urban community culture. The population were the in controlled hypertension elders in an urban community. Samples were 44 elders diagnosed as hypertension and treated more than 10 years with medicine prescribed by the physician. They volunteered to participate to the focus groups. The samples denied to have any hypertension complications within one year before the data collection period. They were tested before participating the focus groups that no dementia or depression. Seven focus groups were conducted with the permission of the samples. Participants’ group discussions were recorded and transcribed. The grounded theory method was used to develop a semi-structured interview guide corresponding to Bertalanfly’s general system model. At the 8th focus group, the interview guide was used to confirm the elders’ health management concepts. Three themes were extracted indicating the health management concept for Thai hypertension elders in urban community. Firstly, the objectives of their health management were getting healthy meaning enable for daily life activities and not depend on their family members; gaining good relationship with friends and families; and having financial afford. Secondly, there were 2 inputs for being well health management : practicing Buddhist path of accomplishment or basis for success (aspiration, exertion, thoughtfulness, and investigation); and having family support and social resources. Finally, eight factors were categorized as both process and outcomes interchangeably indicating the controlled hypertension elders’ good health management : 1) aerobic exercise, 2) no oily and salty but high fiber food, 3) no alcohol, 4) controlledbody weight 5) no smoking 6) stress management using relaxation 7) taking medication as the routine, and 8) peer group supports. The implications for practice, education, research, and policy makers, and the limitations of the study were discussed.